THE EFFECTIVENESS OF LINGUISTIC TRANSFORMATIONS IN SIMULTANEOUS INTERPRETING (BY THE EXAMPLES OF UZBEK-ENGLISH OFFICIAL DISCOURSE) (International Conference on Education, Psychology and Humanities, 2026)
Simultaneous interpreting (SI) is a cognitively intensive linguistic activity that requires rapid processing, reformulation, and delivery of speech across languages. One of the core mechanisms enabling interpreters to cope with time pressure and structural asymmetry between languages is the application of linguistic transformations. This study investigates the effectiveness of linguistic transformations in English–Uzbek simultaneous interpreting within official and institutional discourse. The research examines the frequency, function, and communicative outcomes of transformations such as compression, transposition, modulation, generalization, explicitation, and omission. Using a mixed qualitative–quantitative approach, authentic samples of English and Uzbek official discourse were analyzed to determine how transformations influence accuracy, fluency, and communicative adequacy. The findings reveal that linguistic transformations are not merely optional stylistic choices but strategic cognitive operations that enhance interpretative efficiency and ensure functional equivalence. Compression and transposition were the most frequently applied strategies, particularly in institutional speeches characterized by complex syntactic structures. The study concludes that effective use of linguistic transformations significantly reduces cognitive load and increases pragmatic clarity in simultaneous interpreting.
Keywords: Simultaneous interpreting; linguistic transformations; compression; transposition; modulation; generalization; explicitation; omission; cognitive load; official discourse; English–Uzbek interpreting; translation strategies; functional equivalence; conference interpreting